مخاوف السيدات ذوات الحمل غير المخطط (Latakia University Journal -Medical Sciences Series, 2017)
هدفت هذه الدراسة إلى تحديد المخاوف الجسمانية والنفسية والمادية والاجتماعية والجنسية للحمل غير المخطط. وقد أجريت هذه الدراسة في عيادة متابعة الحوامل في مستشفى التوليد والأطفال في محافظة اللاذقية, و شملت 170سيدة مع حمل غير مخطط تم اختيارهن بالطريقة المناسبة من المكان السابق الذكر. تمجمع البيانات الخاصة بالبحثعن طريق استخدام استمارة استبيان مطورة من قبل الباحث. وقد أظهرتالنتائج أن 41% من السيدات قد سبب لهن الحمل غير المخطط مشاكل جسمانية، 74% منهنَشعرت بالحزن الشديد، 24% تقريباﹰ منهنَ أحسسن بالإحباط. كذلك سبب الحمل الحالي غير المخطط له مشاكل اجتماعية ل 49% من السيدات، مشاكل مادية ل62% منهنَ.كذلك أظهرت نتائج الدراسة الحالية أنَ الحمل غير المخططله قد أثَر على العلاقة الجنسية بين السيدات وأزواجهن. لذلك نقترح إجراء دورات حول التثقيف الجنسي الشامل وضرورة استخدام وسائل تنظيم الأسرة وتسهيل الوصول إلى خدمات تنظيم الأسرة بشكل واسع،ضرورة إجراء أبحاث لمعرفة نسبة انتشار الحمول غير المخطط لها في مجتمعنا واتخاذ الإجراءات والتدابير المناسبة لتقليل ومنع الحمول غير المخطط لها.The aim of the study was to identify physical, psychological, socioeconomic and sexual concerns. This study was conducted in the antenatal clinic at children and obstetric hospital in Lattakia City. A convenient sample of 170 women with unplanned pregnancy attending the previously mentioned setting was included in the study. Questionnaire sheet was developed by researcher and used to collect the necessary data. The results of this study revealed that 41.18% of women have physical problems due to unplanned pregnancy, 74% of them have sad feeling and about 24%have depressed feeling. Also unplanned pregnancy cause social problems in 49% of women, financial problems in 62% of them. The results of this study also revealed that unplanned pregnancy affect sexual relationship between women and their partners. So we suggest comprehensive sexual education, availability of family planning services and increased access to a range of effective birth control methods. and must evaluate the incidence of unplanned pregnancy in our society and make proper action to reduce and prevent the occurrence of unplanned pregnancy.